Health conditions and disability-related factors in older adults -A reflection for care- - Calvo-Soto, Andrea Patricia; Gómez-Ramírez, Esperanza (Universidad y Salud, 2018)
Introduction: The situation in the world of the growth of the older adult population is clear. Ageing also brings with it a burden of important chronic diseases, where cardiovascular, mental health and cancer diseases are among the prevalent. In addition, the need for assistance from these people in the long term is increased because mobility is lost, fragility increases and physical or mental illnesses sequelae enhance the rates of disability. Objective: To reflect on the aspects of health and disability of older adults as reported in the literature. Materials and methods: Literature review of articles of specialized scientific databases and academic repositories, using logical descriptors and boolean operators related to the subject. Results: The information was structured taking into account the aspects related to the health status of older adults, the condition of disability, risk and protective factors. Conclusions: Early diagnosis of prevalent diseases in older adults is supported by defining the risk factors of disability but emphasizing the intervention based on healthy aging.